2004
DOI: 10.4161/cc.3.9.1090
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Glial Numbers and Axonal Patterns

Abstract: The control of the rate of cell division enables cells to respond to signals from other cells and this promotes the emergence of order as cell mass increases during growth. Glial cell proliferation is coupled to axon guidance, and the sequential deployment of glial cells in constrained numbers enables the sequential sorting out of axons into appropriate trajectories through time. 1 This is achieved by the neuron-dependent regulation of glial division at the G 1 phase. Early on, Prospero plays a key role contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…CNS glia migrate extensively between stages 13 and 16, so that glial nuclear patterns undergo rapid changes (reviewed by (Hidalgo and Griffiths, 2004)). At late stage 16, glial nuclei in the focal plane of Figure 7F are organized in a semi-regular lattice in wild-type embryos, with two rows of nuclei extending along each longitudinal tract and a segmentally repeated pattern of nuclei closer to the midline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CNS glia migrate extensively between stages 13 and 16, so that glial nuclear patterns undergo rapid changes (reviewed by (Hidalgo and Griffiths, 2004)). At late stage 16, glial nuclei in the focal plane of Figure 7F are organized in a semi-regular lattice in wild-type embryos, with two rows of nuclei extending along each longitudinal tract and a segmentally repeated pattern of nuclei closer to the midline.…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal axon guidance and interface glial development are intertwined processes (for review see (Hidalgo and Griffiths, 2004)). Perturbation of interface glia can cause longitudinal axons to cross the midline (Kinrade and Hidalgo, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with studies of pros mutants, which found a role for Pros earlier in CNS development in establishing glial cell number . The role of Pros in mature LG is poorly understood, but it has been proposed to retain mitotic potential in these cells for use in repair or remodeling of the nervous system in subsequent larval or adult stages Hidalgo and Griffiths, 2004). It will be important to determine the consequences of lost Pros expression from mature anterior LG, and whether additional features and functions of the anterior LG are controlled by N signaling from axons.…”
Section: Discussionmentioning
confidence: 99%
“…During nervous system development in Drosophila, glial cells are important for neuron survival and for the guidance, pruning and ensheathment of axons; in return, neurons provide trophic support for glia, stimulate glial proliferation and guide glial migrations (Booth et al, 2000;Chotard and Salecker, 2004;Hidalgo and Griffiths, 2004;Klambt et al, 2001). Although progress has been made in understanding cellular aspects of neuron-glial interactions, the molecular signals that regulate communication between neurons and glial cells remain largely undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Es posible que estas células, descritas también en el carpín (Sánchez-González, 2009), sean gliales, ya que son elúnico grupo celular con capacidad de división que se sitúa en dicha capa. En apoyo de lo anterior, conviene resaltar que ya se ha descrito la expresión de Prox1 tanto en células gliales en el cerebro de Drosophila melanogaster (Hidalgo y Griffiths, 2004) como en el giro dentado del ratón (Lavado y Oliver, 2007).…”
Section: Colocalización De Prox1 Con Brduunclassified